Reporte De Caso Clínico F.L.U.T.D. En Un Felino Informe De Pasantía En La Clínica Veterinaria En Bogota (2024)
This document was prepared in order to present the work carried out during the period from September to October 2024 in the Clinic facilities Veterinaria Verde Animal, and presents a case report of the pathology (Feline Lower Urinary Tract Disease) FLUTD English). This work documents the practice that was developed in order to acquire practical and theoretical skills in the field of medicine veterinary medicine, specifically in the management of small animals.